2010
DOI: 10.1097/pec.0b013e3181e5bf85
|View full text |Cite
|
Sign up to set email alerts
|

Toothpick Ingestion Causing Duodenal Perforation

Abstract: In childhood, almost all swallowed objects that successfully navigate the esophagus pass through the gut without complications. In a 15-year-old male adolescent with the initial working diagnosis of acalculous cholecystitis, computed tomography revealed a thickened wall of the second duodenal portion, some infiltration of the periduodenal tissue, and a hyperdense needle-shape structure probably passing through the duodenal wall. Endoscopy revealed a wooden toothpick perforating the duodenum that was carefully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 4 publications
0
22
0
2
Order By: Relevance
“…Perforation is common with sharp objects, but blunt objects can also cause perforation, due to pressure necrosis secondary to local inflammation [5]. Ragazzi et al [11] reported a case of duodenal perforation from a toothpick that had an uneventful recovery mediated by endoscopic removal. Endoscopic clipping has increasingly been used for closure of small duodenal perforation, and cases were reported where successful closure of a perforation was achieved by endoscopic clipping, especially with iatrogenic perforation [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Perforation is common with sharp objects, but blunt objects can also cause perforation, due to pressure necrosis secondary to local inflammation [5]. Ragazzi et al [11] reported a case of duodenal perforation from a toothpick that had an uneventful recovery mediated by endoscopic removal. Endoscopic clipping has increasingly been used for closure of small duodenal perforation, and cases were reported where successful closure of a perforation was achieved by endoscopic clipping, especially with iatrogenic perforation [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…However, a nonsurgical strategy can be successful in certain cases. A successful conservative treatment in a case of a duodenal perforation, identified several days after the ingestion of a toothpick by a 15-year-old boy, has been reported 11. Since Binmoeller et al12 reported a case of endoscopic closure of an iatrogenic gastric perforation by using metallic clips in 1993, attempts on managing bowel perforation nonsurgically have been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation from a swallowed toothpick is a rare [1][2][3][4] but potentially life-threatening event. Since most of the time the patient is unaware of having ingested a toothpick, the diagnosis is difficult [5][6][7].…”
Section: Supporting Informationmentioning
confidence: 99%